2020
DOI: 10.14808/sci.plena.2020.020204
|View full text |Cite
|
Sign up to set email alerts
|

Cheese whey as potential medium fermentation to Saccharomyces fragilis IZ 275 yeast

Abstract: Yeasts β-galactosidase is intracellular enzyme, show a high lactose hydrolyzing capacity and therefore can be used to reduce the level of lactose of milk and dairy products. However, the activity of β-galactosidase, or its production, is strongly influenced by carbon availability as source of energy. The aim of this work was to compare different carbons source with the cheese whey, by-product of dairy industry and potential source to grow microorganism, and its interactions as fermentation mediums to productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This could be due to the CWP composition (salts, proteins and small amounts of vitamins) that could have a positive effect on the biomass production. There are few reports on the production of yeast biomass from CWP as a substrate (Barba et al, 2001;Bosso et al, 2020;Prajapati et al, 2017). The biomass yield coefficient (Y X/S ) obtained in this work (0.44-0.77 g B /g S ) was similar or better than those reported previously in literature, with different carbon and nitrogen sources (Ariyanti & Hadiyanto, 2013;Fonseca et al, 2007;Kurniawati et al, 2022;Bosso et al, 2019;Ferrari et al, 2001;Cristiani-Urbina et al, 2000;Schnierda et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This could be due to the CWP composition (salts, proteins and small amounts of vitamins) that could have a positive effect on the biomass production. There are few reports on the production of yeast biomass from CWP as a substrate (Barba et al, 2001;Bosso et al, 2020;Prajapati et al, 2017). The biomass yield coefficient (Y X/S ) obtained in this work (0.44-0.77 g B /g S ) was similar or better than those reported previously in literature, with different carbon and nitrogen sources (Ariyanti & Hadiyanto, 2013;Fonseca et al, 2007;Kurniawati et al, 2022;Bosso et al, 2019;Ferrari et al, 2001;Cristiani-Urbina et al, 2000;Schnierda et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…As a result, the medium optimized with CWP is a suitable culture medium to produce a valuable product such as yeast biomass. CWP is an excellent source of functional proteins, peptides, lipids, vitamins, minerals, and lactose (Bosso et al, 2020;Prajapati et al, 2017;Ryan & Walsh, 2016;Vamvakaki et al, 2010). In addition, some authors demonstrated that the addition of (NH 4 ) 2 SO 4 and KH 2 PO 4 increased biomass yield and biomass production (Cristiani-Urbina et al, 2000;Galvagno et al, 2011;Vamvakaki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation